2005
DOI: 10.1038/nn1410
|View full text |Cite
|
Sign up to set email alerts
|

Multiple periods of functional ocular dominance plasticity in mouse visual cortex

Abstract: The precise period when experience shapes neural circuits in the mouse visual system is unknown. We used Arc induction to monitor the functional pattern of ipsilateral eye representation in cortex during normal development and after visual deprivation. After monocular deprivation during the critical period, Arc induction reflects ocular dominance (OD) shifts within the binocular zone. Arc induction also reports faithfully expected OD shifts in cat. Shifts towards the open eye and weakening of the deprived eye … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
227
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(259 citation statements)
references
References 43 publications
30
227
2
Order By: Relevance
“…Such sensory manipulation produced unilateral activation of the V1, as visualized by high immunoreactivities of endogenous Arc/Arg-3.1 at layers 2/3 and 4 in the contralateral, but not in the ipsilateral, visual cortex ( Fig. 6B) (21). Consistent with this pattern, we found that the majority (58.3 Ϯ 7.9%) of RFP-positive neurons were GFP-positive in the contralateral hemisphere that received visual inputs, whereas only a small number (19.3 Ϯ 4.4%) of neurons were positive in the ipsilateral hemisphere ( Fig.…”
Section: Visualization Of Activated Cells In a Neuronal Circuit Usingmentioning
confidence: 97%
See 2 more Smart Citations
“…Such sensory manipulation produced unilateral activation of the V1, as visualized by high immunoreactivities of endogenous Arc/Arg-3.1 at layers 2/3 and 4 in the contralateral, but not in the ipsilateral, visual cortex ( Fig. 6B) (21). Consistent with this pattern, we found that the majority (58.3 Ϯ 7.9%) of RFP-positive neurons were GFP-positive in the contralateral hemisphere that received visual inputs, whereas only a small number (19.3 Ϯ 4.4%) of neurons were positive in the ipsilateral hemisphere ( Fig.…”
Section: Visualization Of Activated Cells In a Neuronal Circuit Usingmentioning
confidence: 97%
“…Detailed analyses of Arc/Arg-3.1 expression using in situ hybridization have revealed that Arc/ Arg-3.1 transcription is specifically triggered by task-or sensory input-related information processing in several brain areas, including the hippocampus, amygdala, and cerebral cortex (19)(20)(21). The shortness of SARE sequence allows designing a virus-based tool to monitor Arc/Arg-3.1 expression for both in vitro and in vivo imaging.…”
Section: Mapping Of Active Ensembles Within a Neuronal Circuit Can Bementioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing consensus, however, that the adult cortex maintains greater plasticity than originally thought (Kaas, 1991;Buonomano and Merzenich, 1998;Gilbert, 1998;Tagawa et al, 2005). For example, monocular deprivation shifts the ocular dominance of neurons in the primary visual cortex of adult mice, although the manner of the shift differs from that observed in juveniles (Sawtell et al, 2003;Frenkel and Bear, 2004;Pham et al, 2004).…”
Section: Introductionmentioning
confidence: 96%
“…Monocular eyelid suture results in anatomical changes in the visual cortex in favor of the non-deprived eye (Wiesel & Hubel, 1965;Tagawa et al, 2005;Cang et al, 2005;Hofer et al, 2006;Lehmann & Löwel, 2008). This phenomenon is referred to as ocular dominance plasticity.…”
Section: Introductionmentioning
confidence: 99%